THE IMPLEMENTATION OF BILINGUAL EDUCATION AT BALI BILINGUAL SCHOOL KINDERGARTEN (A Case Study) - Komang Ary Purwanti; Pande Agus Adiwijaya; I Putu Suyoga Dharma (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2020)
This research aimed at to know 1) how the planning of bilingual education in teaching and learning process at Bali Bilingual School kindergarten; 2) how the implementation of bilingual education in teaching and learning proses especially for early childhood at Bali Bilingual School kindergarten; 3) how the evaluation of bilingual education in teaching and learning process at Bali Bilingual School kindergarten. This research used case study method and qualitative approach for about two months. As for the data collection techniques were used observation, interviews and documentation. The data analysis activity consisted of three simultaneous activity flow, namely data reduction, data display, and conclusion/verification. The research findings are 1) lesson planning is not accordance with the criteria of bilingual program because it is only made in Indonesia; 2) implementation of bilingual education in teaching and learning process is not done optimally; 3) learning evaluation is not accordance with the criteria of bilingual program because it is only made in Indonesia. Based on the research findings, it can be concluded that the implementation of bilingual education in Bali Bilingual School kindergarten both from the planning, teaching learning process, and learning evaluation has not run optimally.